What they contribute case studies on the impact of nonprofit organizations - Carino, Ledivina V.; Gaffud, Dolores D. (Center for Leadership, Citizenship and Democracy, National College of Public Administration and Governance, University of the Philippines, 2007)
"This book is a collection of case studies on nine nonprofit organizations in the Philippines. As a very small sample of an estimated half million organizations in the country, they cannot claim to be representative. Neverthless, they offer a glimpse of the complexity of present-day civil society and can give insights on what the sector can contribute to state and society as they perform their various activities and programs."--Introduction.